Determinants Of Tax Aggressiveness - Harefa, Meilinda Stefani; Lumban Gaol, Vebry M. (LPPM Universitas HKBP Nommensen, 2024)
This study aims to examine the factors that influence tax aggressiveness in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). The variables used in this study are profitability (ROA), leverage, company size (size). The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The sample in this study was selected using purposive sampling, and 63 data were taken. The data was analyzed using SmartPLS. The results of this study indicate that profitability and leverage have a positive and significant effect on tax aggressiveness while company size has no effect on tax aggressiveness.